Entomophagy and Italian consumers: an exploratory analysis - Sogari, Giovanni (Progress in Nutrition, 2015)
Background and aim of the work: the consumption of insects by humans, entomophagy, is a food practice followed by 2 billion people worldwide. However, in Western countries the majority of the population rejects the idea of adopting insects as food, predominantly for cultural reasons. This study aims to investigate the main reasons behind this in order to stimulate the consumption of edible insects in the future. Methods: the experiment involved a mixed group of Italian individuals (n=46) – in terms of age and gender – who tasted three species of edible insects (cricket, honeycomb moth and grasshopper) and afterwards were handed a questionnaire to explore their opinions on the subject of entomophagy. Results: the analysis shows that curiosity and environmental benefits are the most important factors in motivating the consumption of insects in the future. Furthermore, the majority of respondents stated that entomophagy would not be endorsed and supported by family and/or friends. Conclusions: although the results of this study are exploratory, it seems that other peoples’ negative opinions might represent a significant barrier to introducing edible insects to the Western diet. For the moment, it is difficult to predict whether edible insects will become the “food of the future”.